Systemic Antibiotics Influence Periodontal Parameters and Oral Microbiota, But Not Serological Markers - Kopra, Elisa; Lahdentausta, Laura; Pietiäinen, Milla; Buhlin, Kåre; Mäntylä, Päivi; Hörkkö, Sohvi; Persson, Rutger; Paju, Susanna; Sinisalo, Juha; Salminen, Aino; Pussinen, Pirkko J. (Frontiers in Cellular and Infection Microbiology, 2021)
The use of systemic antibiotics may influence the oral microbiota composition. Our aim was to investigate in this retrospective study whether the use of prescribed antibiotics associate with periodontal status, oral microbiota, and antibodies against the periodontal pathogens. The Social Insurance Institution of Finland Data provided the data on the use of systemic antibiotics by record linkage to purchased medications and entitled reimbursements up to 1 year before the oral examination and sampling. Six different classes of antibiotics were considered. The Parogene cohort included 505 subjects undergoing coronary angiography with the mean (SD) age of 63.4 (9.2) years and 65% of males. Subgingival plaque samples were analysed using the checkerboard DNA-DNA hybridisation. Serum and saliva antibody levels to periodontal pathogens were analysed with immunoassays and lipopolysaccharide (LPS) activity with the LAL assay. Systemic antibiotics were prescribed for 261 (51.7%) patients during the preceding year. The mean number of prescriptions among them was 2.13 (range 1–12), and 29.4% of the prescriptions were cephalosporins, 25.7% penicillins, 14.3% quinolones, 12.7% macrolides or lincomycin, 12.0% tetracycline, and 5.8% trimethoprim or sulphonamides. In linear regression models adjusted for age, sex, current smoking, and diabetes, number of antibiotic courses associated significantly with low periodontal inflammation burden index (PIBI, p < 0.001), bleeding on probing (BOP, p = 0.006), and alveolar bone loss (ABL, p = 0.042). Cephalosporins associated with all the parameters. The phyla mainly affected by the antibiotics were Bacteroidetes and Spirochaetes. Their levels were inversely associated with the number of prescriptions (p = 0.010 and p < 0.001) and directly associated with the time since the last prescription (p = 0.019 and p < 0.001). Significant inverse associations were observed between the number of prescriptions and saliva concentrations of Prevotella intermedia, Tannerella forsythia, and Treponema denticola and subgingival bacterial amounts of Porphyromonas gingivalis, P. intermedia, T. forsythia, and T. denticola. Saliva or serum antibody levels did not present an association with the use of antibiotics. Both serum (p = 0.031) and saliva (p = 0.032) LPS activity was lower in patients having any antibiotic course less than 1 month before sampling. Systemic antibiotics have effects on periodontal inflammation and oral microbiota composition, whereas the effects on host immune responses against the periodontal biomarker species seem unchanged.